Confirmatory Factor Analysis of Religious Outreach According to Seventh-day Adventist Principles among Undergraduate Students at Asia-Pacific International University - Plainetr, Prapai; Choochom, Oraphin; Kijthorntham, Wichuda (Human Behavior, Development and Society, 2019)
The objective of this research study was to analyze confirmatory factors of religious outreach according to Seventh-day Adventist principles among undergraduate students at Asia-Pacific International University by survey research. The sample was comprised of 567 Seventh-day Adventist undergraduate students studying in the second semester of the 2015 academic year. The members of the sample were selected by judgmental sampling, and the data were collected by using an instrument comprised of items that used a six-point rating scale and had a reliability level of 0.883. In addition, descriptive statistics were used to analyze the data, and LISREL was used to confirm and analyze the factors. The research results showed that religious outreach according to Seventh-day Adventist principles is consistent with the empirical data after adjusting the model. The factor loading range for each question was between 0.64 to 0.84, and religious outreach practice according to Seventh-day Adventist principles was conveyed by speech, by writing, and by role modeling.